Disputas por la ciudadanía laboral: Precarización y lucha por derechos en la profesión docente de primaria en Guatemala: Libro de Leslie Lemus Barahona - Ramírez Ceballos, Estefanía (El Colegio de México, 2025)
This study falls within the field of labor, citizenship, and the teaching profession. It examines the configuration of Guatemala’s primary school teaching labor market and the resulting constraints on the exercise of rights by its members, within the context of structural adjustment policies that shaped a fragile labor citizenship status for primary school teachers. Beyond its thematic contributions, this research also offers valuable and inspiring methodological insights for developing processual and relational analyses across other areas of the social sciences. This review explores these dimensions as a means of fostering broader scholarly dialogue within the field.